2016
DOI: 10.1016/j.psyneuen.2016.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Low dose intranasal oxytocin delivered with Breath Powered device dampens amygdala response to emotional stimuli: A peripheral effect-controlled within-subjects randomized dose-response fMRI trial

Abstract: This trial is registered at the U.S. National Institutes of Health clinical trial registry (www.clinicaltrials.gov; NCT01983514) and as EudraCT no. 2013-001608-12.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
89
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(103 citation statements)
references
References 67 publications
11
89
1
2
Order By: Relevance
“…71 Research is increasingly pointing towards lower oxytocin doses being more (or at least equivalently) efficacious than higher doses. 36,37,72,73 The present result also adds to existing behavioral 40 and neural 41 evidence that lower oxytocin doses delivered with the Breath Powered device may be more efficacious, at least for single administration trials. Alternatively, 24IU oxytocin delivered via traditional nasal devices may offer equivalent central levels because of substantial loss of the delivered drug.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…71 Research is increasingly pointing towards lower oxytocin doses being more (or at least equivalently) efficacious than higher doses. 36,37,72,73 The present result also adds to existing behavioral 40 and neural 41 evidence that lower oxytocin doses delivered with the Breath Powered device may be more efficacious, at least for single administration trials. Alternatively, 24IU oxytocin delivered via traditional nasal devices may offer equivalent central levels because of substantial loss of the delivered drug.…”
Section: Discussionsupporting
confidence: 56%
“…Moreover, neural evidence from the same data set also suggested that intranasal 8IU (but not the other oxytocin treatments) reduced amygdala activation during the presentation of social stimuli. 41 Another barrier to the translation of pre-clinical oxytocin research relates to the study design issues. Many oxytocin studies are statistically underpowered, with clinical studies having an average of 12% statistical power to detect the median Cohen's d of 0.32.…”
Section: Introductionmentioning
confidence: 99%
“…Although intranasal oxytocin administration increased salivary (van IJzendoorn, Bhandari, van der Veen, Grewen, & Bakermans-Kranenburg, 2012), plasma (Striepens et al, 2013) and cerebrospinal fluid (Striepens et al, 2013) concentrations of oxytocin, it remains unknown whether these observations reflect amplified endogenous oxytocin release upon intranasal oxytocin administration (potentially as a result of positive feedback mechanisms (Ludwig, 2014; van IJzendoorn et al, 2012)) or the exogenously administered compound. However, recent studies in which oxytocin was administered both intravenously and intranasally suggest a direct nose-to-brain route for oxytocin (Quintana, Alvares, Hickie, & Guastella, 2015; Quintana et al, 2016). In addition, the exact duration of oxytocin administration effects on brain function, stress reactivity and socio-emotional behaviour remain unknown, although it was recently demonstrated that neural effects of intranasal oxytocin may be observed up to at least 80 min post-administration (Paloyelis et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Yes, as I mentioned briefly earlier, we've published a study in healthy volunteers in Phase I studies, where we had an intravenous oxytocin comparison [14,15]. Here we had a placebo and two different doses of oxytocin delivered to the volunteers using our device.…”
Section: How Does Optinose Delivery Technology Hope To Overcome the Dmentioning
confidence: 99%
“…We delivered oxytocin via the intranasal and also the intravenous route as a comparison [14,15]. Despite similar levels in the blood, significant differences in cognitive tests and corresponding brain activation were observed.…”
Section: How Does Optinose Delivery Technology Hope To Overcome the Dmentioning
confidence: 99%